Exploring configurations of social determinants for enhancing older adult health in China: an fuzzy-set qualitative comparative analysis based on 31 provinces in China - Zhang, Songbiao; Wang, Xining; Wang, Huilin (Frontiers in Public Health, 2023)
With China's aging population on the rise, addressing population aging has become a national priority, particularly focusing on improving elderly health. This study employs the social determinants of health framework, considering China's unique macro-social, economic, policy, healthcare, and family cultural factors, to develop a framework for understanding the social determinants of health for older adults in China. Using the fsQCA method and a configurational perspective, the complex relationship between social determinants of health and elderly health status is examined. The findings indicate that individual social determinants alone are insufficient for achieving high levels of elderly health. Instead, three configurations of social determinants have been identified as conducive to high elderly health:dominant economic development, a combination of economic development and social elderly care, and a combination of social-economic development and family elderly care. Economic Development-Environment -Cultural Dominant Type, Socio-Economic Development -Elderly Security -Environment -Cultural Dominant Type, and Economic Development Dominant Type. These configurations offer diverse pathways for enhancing elderly health. Conversely, the study identifies two configurations associated with low elderly health levels, exhibiting an asymmetric relationship with the configurations resulting in high elderly health levels. Moreover, economic development consistently emerges as a core condition across all three configurations associated with high elderly health levels, while two configurations associated with low elderly health lack this core condition. These findings underscore the universal contribution of enhancing economic development to improving elderly health.